1997
DOI: 10.1038/bjc.1997.69
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of recombinant interferon-β (r-hIFN-β 1a) in combination with 5-fluorouracil (5-FU) in the treatment of patients with advanced colorectal carcinoma

Abstract: Summary The combination of 5-fluorouracil (5-FU) and interferon-alpha (IFN-a) has reported activity in the treatment of advanced colorectal carcinoma. Laboratory studies of IFN-n suggest that this agent may offer theoretical advantages over IFN-a in combination with 5-FU. A total of 27 patients with advanced or recurrent colorectal carcinoma were treated in a non-randomized open phase 11 study with a combination of 5-fluorouracil (750 mg m-1 daily for 5 days as a continuous intravenous (i.v.) infusion followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The protein has been delivered by intramuscular, intravenous, or intratumoral routes, with common toxicities including myelosuppression, transaminitis, and neurotoxicity (include seizures), indicating that localized, tumor-specific delivery of the cytokine would be desirable. Antitumoral efficacy was reported, however, both in patients with brain tumors (including glioblastoma multiforme) [ 34 , 35 ] and in a patient with colorectal carcinoma [ 36 ]. IFN-β therefore represents a promising cytokine for use in cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The protein has been delivered by intramuscular, intravenous, or intratumoral routes, with common toxicities including myelosuppression, transaminitis, and neurotoxicity (include seizures), indicating that localized, tumor-specific delivery of the cytokine would be desirable. Antitumoral efficacy was reported, however, both in patients with brain tumors (including glioblastoma multiforme) [ 34 , 35 ] and in a patient with colorectal carcinoma [ 36 ]. IFN-β therefore represents a promising cytokine for use in cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Other drugs recently have been tested in patients with CRC, but with negative results. These include the somatostatin analogue octreotide108; tallimustine, a novel DNA minor groove binder109; edatrexate, a methotrexate analogue110; the addition of interferon‐ß to 5‐FU111; and several new drugs that have shown definite activity in other types of cancer such as paclitaxel,112 docetaxel,113, 114 and gemcitabine 115…”
Section: Chemotherapeutic Agentsmentioning
confidence: 99%
“…Various regimens of chemotherapy include 5-fluorouracil (5-FU), irinotecan (CPT-11) and so on, (2,3) but the results have not been satisfactory yet. Under this situation, some studies reported that chemotherapies with interferon (IFN)-ß were effective for patients with advanced colorectal carcinoma (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%